Quasi-Resonant Half-Wave Buck Converter with Non-Isolated High Side Switching Techniques - Elif Topuz; Burak Gördük; Deniz Yıldırım (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Power density of the power converters became one of the most important parameters in many applications. Power density is increased by reducing the losses through use of better performing components and circuit topologies. It can be increased further by reducing the size of filter components through increasing the switching frequency. In hard-switching converters however, losses due to switching will eventually render this method not applicable. Instead, resonant converters are utilized in many high-frequency switched power supplies. Soft-switching feature of these converters provide increased efficiency due to decreased switching losses. Such converters exploit the resonance of the specific inductors and capacitors in the circuit called as resonant tank elements. Resonance behavior is used in order to eliminate turn-on or turn-off losses. Existing power converter topologies can be modified to create the resonance during switching period. Such converters are called as quasi-resonant converters. This paper presents analysis and design of Zero Current Switching (ZCS) half-wave quasi-resonant buck converters. In this topology, high-side switching is required. Two different non-isolated high-side switching techniques are utilized. Experimental results are obtained for light load to full load operation. Both techniques are compared in detail.